1977
DOI: 10.2172/5276204
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic Technique for Rapid Inventory of Plutonium-Containing Fast Critical Assembly Fuel

Abstract: 16 bus w Pw d. md ofE bm. w w oft @NOW gqw ". 6* mwAims. w~wweai a r3m qiqss w aw mn*l. uw «Si 00-wwwr a whomm Gr.v wMw. "N. Peda w pm. ibbli. a wUwU "M INm w .m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1978
1978

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…2 ' 3 Recently, autoradiographic methods have been applied to inventory verifications of plutoniumcontaining fast critical assembly fuel, 4 and one study reported the examination of low-enriched uranium fuel rods. 5 The method is based on the ability of spontaneously emitted X-and gamma radiation from uranium-containing fuel elements to expose photographic film.…”
Section: Autoradiographymentioning
confidence: 99%
See 1 more Smart Citation
“…2 ' 3 Recently, autoradiographic methods have been applied to inventory verifications of plutoniumcontaining fast critical assembly fuel, 4 and one study reported the examination of low-enriched uranium fuel rods. 5 The method is based on the ability of spontaneously emitted X-and gamma radiation from uranium-containing fuel elements to expose photographic film.…”
Section: Autoradiographymentioning
confidence: 99%
“…The methods used for obtaining images of plutonium-containing fuel elements required only 15-to 45-minute exposures, depending on the source-film distance and the absorber thickness. 4 If these same methods are used for low-enriched U-235-containing fuel elements, exposure times of several days are required to obtain equal image density for equal fissile content. Such long exposure times are obviously not useful in an inventory technique which must be applied by inspectors in the field.…”
Section: Minimization Of Exposure Timementioning
confidence: 99%